Impact of COVID-19 pandemic on the existence of social solidarity: evidence from rural-urban communities in Lombok Island, Indonesia - Sayuti, Rosiady H.; Taqiuddin, Moh; Evendi, Azhari; Hidayati, Siti Aisyah; Muttaqin, M. Zaenul (Frontiers in Sociology, 2023)
The COVID-19 pandemic that has hit the entire world since the beginning of 2020 is unimaginable. The pandemic is disastrous because it has caused loss of life and livelihood for a large part of the population. People lose their jobs, spaces for social interaction are closed, and social relationships are disrupted. Several studies show that social solidarity should be a major concern for people to sustain the future quality of their lives. Social solidarity dimensions in this study include gotong royong, marriage banjars, cooperation, mutual help, and information sharing. This study aims to examine the existence of social solidarity during the pandemic in rural and urban areas and to know the level of community exposure to Covid-19 in Lombok Island, Indonesia. This research adopted a quantitative approach to identify and analyze the existence of social solidarity in rural and urban communities during the COVID-19 pandemic. A set of questionnaires was distributed and shared by enumerators with 1,100 targeted respondents from Lombok Island. The survey was carried out from 14th October to 28th October 2021, that is, during a recovery period from the pandemic while restrictions implemented by the government were still in full force. Chi-square statistical analysis was used to test whether there were differences in social solidarity between those who lived in rural areas and those who lived in urban areas. This research found the existence of social solidarity in both rural and urban communities during the pandemic. The level of social solidarity in rural areas is higher than in urban areas. While related to the number of those who were exposed and died, conditions were higher in rural areas than in urban areas. However, in terms of the death rate, the level of death rate in urban areas is higher than in rural areas. This condition indicates differences in the characteristics of rural and urban communities, which can be considered in implementing policies during a future pandemic. This research provides evidence for local governments to formulate policies with a social solidarity perspective by considering the different characteristics of rural and urban communities.